Sexism Representation “Train her to be an Ideal Housewife” Ads: Sara Mills Theory - Supriyono, Nanda Meg Ryan Puspitasari; Mathew , Raisun (Lingua : Journal of Linguistics and Language, 2024)
This study examines linguistic sexism and the portrayal of women in Indian advertising media. It aims to highlight how advertisements reinforce gender stereotypes and contribute to societal inequality. The research employs a qualitative approach with descriptive analysis, using Sara Mills' discourse-level analysis theory from Feminist Stylistics (1995) as the analytical framework. The analysis identifies indirect sexism and the objectification of women in advertising. Women are frequently depicted as housewives rather than independent individuals with career aspirations. These portrayals reinforce traditional gender roles, limiting women's representation in diverse professional and social spheres. The study concludes that gender equality remains unachieved in Indian advertising media, as women continue to be stereotyped and confined to domestic roles. The persistence of these portrayals reflects deep-rooted societal biases that restrict women’s opportunities. By shedding light on gender bias in advertising, this study emphasizes the need for more inclusive and equitable media representations. Addressing these stereotypes can contribute to social change and the promotion of gender equality in India.